Concurrent measurements of size-segregated particulate sulfate, nitrate and ammonium using quartz fiber filters, glass fiber filters and cellulose membranes. (November 2016) - Tian, Shili; Pan, Yuepeng; Wang, Jian; Wang, Yuesi
Abstract: Current science and policy requirements have focused attention on the need to expand and improve particulate matter (PM) sampling methods. To explore how sampling filter type affects artifacts in PM composition measurements, size-resolved particulate SO4 2−, NO3 − and NH4 + (SNA) were measured on quartz fiber filters (QFF), glass fiber filters (GFF) and cellulose membranes (CM) concurrently in an urban area of Beijing on both clean and hazy days. The results showed that SNA concentrations in most of the size fractions exhibited the following patterns on different filters: CM > QFF > GFF for NH4 + ; GFF > QFF > CM for SO4 2− ; and GFF > CM > QFF for NO3 − . The different patterns in coarse particles were mainly affected by filter acidity, and that in fine particles were mainly affected by hygroscopicity of the filters (especially in size fraction of 0.65–2.1 μm). Filter acidity and hygroscopicity also shifted the peaks of the annual mean size distributions of SNA on QFF from 0.43–0.65 μm on clean days to 0.65–1.1 μm on hazy days. However, this size shift was not as distinct for samples measured with CM and GFF. In addition, relative humidity (RH) and pollution levels are important factors that can enhance particulate size mode shifts of SNA on clean and hazy days. Consequently, the annual mean size distributions of SNA had maxima at 0.65–1.1 μm for QFF samples and 0.43–0.65 μm for GFF and CM samples. Compared with NH4 + and SO4 2−, NO3 − is more sensitive to RH and pollution levels, accordingly, the annual mean size distribution of NO3 − exhibited peak at 0.65–1.1 μm for CM samples instead of 0.43–0.65 μm. These methodological uncertainties should be considered when quantifying the concentrations and size distributions of SNA under different RH and haze conditions.